On inversion of H-transform in 𝔏v,r-space - Sergei A. Shlapakov; Megumi Saigo; Anatoly A. Kilbas (International Journal of Mathematics and Mathematical Sciences)
The paper is devoted to study the inversion of the integral transform (Hf)(x)=∫0∞Hp,qm,n[xt|(ai,αi)1,p(bj,βj)1,p|]  f(t)dt involving the H-function as the kernel in the space 𝔏v,r of functions f such that ∫0∞|tυf(t)|rdtt<∞  (1<r<∞,ν∈ℝ).